Taxonomic corrections for Asian Fingulus (Hemiptera: Heteroptera: Miridae) - Wang, Yang; Chen, Ling; Rédei, Dávid (Zootaxa, 2021)
The identities of two East and Southeast Asian species of the plant bug genus Fingulus Distant, 1904 (Hemiptera: Heteroptera: Miridae: Deraeocorinae: Deraeocorini) are clarified based on their type specimens. The following new subjective synonymies are proposed: F. longicornis Miyamoto, 1965 = F. brevirostris Ren, 1983, syn. nov.; and F. ruficeps Hsiao & Ren, 1983 = F. henrytomi Nakatani & Yasunaga, 2018, syn. nov. Previous records of F. umbonatus Stonedahl & Cassis, 1991 from Hainan, China, and F. collaris Miyamoto, 1965 from Zhejiang and Yunnan, China, are regarded as misidentifications of F. ruficeps and F. inflatus Stonedahl & Cassis, 1991, respectively.